2017
DOI: 10.1590/s1806-92902017000300012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and influence of production factors on growing and finishing pig farms in Brazilian cooperatives

Abstract: -The objective of this study was to identify and quantify, through mathematical models, the main factors of production in growing and finishing pig units linked to three Brazilian cooperatives located in Western Region of Paraná State that influence the parameters of daily feed intake and feed conversion ratio. The records of 216 growing and finishing farms from 2010 to 2013, representing 1,533 batches, and totaling approximately 1,025,000 pigs, were evaluated. Thirty production factors related to the manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The author also reported a great participation of family workforce in pig farming as well as other economical enterprises within the farm such as crop, cattle, and poultry production. The great importance of the family workforce was also reported by Silva et al (2017) who observed about 75% of the workforce of this type in productive swine farms in the southern region of Brazil.…”
Section: Discussionmentioning
confidence: 53%
“…The author also reported a great participation of family workforce in pig farming as well as other economical enterprises within the farm such as crop, cattle, and poultry production. The great importance of the family workforce was also reported by Silva et al (2017) who observed about 75% of the workforce of this type in productive swine farms in the southern region of Brazil.…”
Section: Discussionmentioning
confidence: 53%
“…On the other hand, the indices of floor type and density, ventilation and temperature of the post-weaning rooms, and water management do not show significant correlations with the studied productivity and health parameters [47], indicating that these management and hygiene indices influence the mortality rate and the productivity during post-weaning. Additionally, some authors propose other management measures or factors [11,13,14], such as the age of the building, to evaluate the air quality and its bacterial load or suggest fewer piglets per pen, which could be included in future versions of this quick scan calculator.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are protocols for assessing animal welfare, such as "Welfare Quality" [10], as well as studies proposing management measures and factors to consider in order to improve the productivity and health outcomes of farms [11][12][13][14] or studies evaluating measures to reduce the use of antimicrobials [5,[15][16][17][18][19][20][21]. In this sense, some of the factors that improve productivity include the number of pigs per pen and the type of feeders [14], as well as biosecurity elements, such as the implementation of an all-in, all-out protocol or the practice of changing clothes and boots between different groups of pigs to prevent infectious diseases [12]. However, there is a need for indices and assessment schemes for overall management and hygiene on farms, which include aspects related to biosecurity, production flow, batch dynamics, a reduction in antimicrobial use, and animal welfare from the handling of facilities perspective.…”
Section: Introductionmentioning
confidence: 99%